Pelatihan Ketrampilan Jumputan Di Tamanharjo, Singosari Kabupaten Malang - Diah Wahyulina; Muhammad Wahid Cahyana; Rumadi Rumadi (Jurnal ABM Mengabdi, 2022)
The Covid 19 pandemic that has hit Indonesia since the beginning of 2020 has not only affected people's freedom to gather, but also affected the people's economic life. Many community members lost their jobs so that the community's economic level declined, this also happened in Tamanharjo Village, Singosari, Malang Regency. The problems faced by the community in Tamanharjo Village, Singosari, Malang Regency as partners of this service program are the desire to develop the creativity of mothers in making jumputans, but they are not supported by capital and there is no adequate knowledge and expertise about making jumputans. Partners need knowledge, techniques and skills to make jumputans based on cloth, which will be very helpful in efforts to produce quality jumputan fabric products, so that they will improve the welfare of the local community. To be able to realize the things mentioned above, assistance and training are needed in making jumputans from cloth. The method that will be used in its implementation is by conducting training on the basics of making jumputan fabrics, introducing equipment and also the practice of making jumputans. The implementation of the jumputan skill making program was carried out well with the results in accordance with the output target of this service, namely partners were able to make and produce jumputan batik fabrics with various patterns and colors, so this can be used as capital to develop jumputan businesses. Keywords: Training, Skills, Cloth, Jumputan, Handmade